2002
DOI: 10.1592/phco.22.9.701.34065
|View full text |Cite
|
Sign up to set email alerts
|

Limited Tolerability of Levofloxacin and Pyrazinamide for Multidrug‐Resistant Tuberculosis Prophylaxis in a Solid Organ Transplant Population

Abstract: Prophylaxis of MDRTB with levofloxacin and pyrazinamide was associated with limited tolerability due to the high frequency of adverse events. While we search for a better tolerated prophylactic regimen, close monitoring for adverse reactions is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…If the clinical situation mirrors our results in mice, susceptibility of the infecting isolate to Z may indicate the potential for short-course therapy of 9 months or less if Z is continued. On the other hand, continuing Z in the face of resistance may not provide any treatment-shortening benefit while increasing the risk of intolerance and/or toxicity, as observed with fluoroquinolone-Z combinations used to treat latent TB infection among MDR-TB contacts (46)(47)(48)(49). Given the favorable interactions between Z and new TB drugs in development and rising concerns over Z resistance among MDR-TB isolates, improved susceptibility testing methods for Z, including genotypic resistance testing, will continue to require attention in the future (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…If the clinical situation mirrors our results in mice, susceptibility of the infecting isolate to Z may indicate the potential for short-course therapy of 9 months or less if Z is continued. On the other hand, continuing Z in the face of resistance may not provide any treatment-shortening benefit while increasing the risk of intolerance and/or toxicity, as observed with fluoroquinolone-Z combinations used to treat latent TB infection among MDR-TB contacts (46)(47)(48)(49). Given the favorable interactions between Z and new TB drugs in development and rising concerns over Z resistance among MDR-TB isolates, improved susceptibility testing methods for Z, including genotypic resistance testing, will continue to require attention in the future (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…However the optimal duration of fluoroquinolone-containing regimens is unknown. Combined and prolonged use of levofloxacin and pyrazinamide has been associated with poor gastrointestinal tolerance [103,104].…”
Section: Treatment Of Active Tb In Transplant Recipientsmentioning
confidence: 99%
“…A report of 48 solid organ transplant recipients who were receiving levofloxacin and pyrazinamide for presumed MDR LTBI revealed that 32 (67%) discontinued therapy prematurely because of adverse events. 151 Gastrointestinal intolerance accounted for more than half of the adverse events. In a case series of 17 persons in Ontario, Canada with suspected MDR LTBI who were treated with levofloxacin and pyrazinamide, all 17 discontinued treatment because of a variety of adverse effects including musculoskeletal, central nervous system, gastrointestinal and dermatologic symptoms.…”
Section: Treatment Of Latent Tuberculosis Infection In Contacts Of Acmentioning
confidence: 99%